Latitudinal gradient in dairy production with the introduction of farming in Atlantic Europe - Cubas, Miriam; Lucquin, Alexandre; Robson, Harry K; Colonese, André Carlo; Arias, Pablo; Aubry, Bruno; Billard, Cyrille; Jan, Denis; Diniz, Mariana; Fernandes, Ricardo; Fábregas Valcarce, Ramón; Germain-Vallée, Cécile; et al. (Nature communications, 2020)
The introduction of farming had far-reaching impacts on health, social structure and demography. Although the spread of domesticated plants and animals has been extensively tracked, it is unclear how these nascent economies developed within different environmental and cultural settings. Using molecular and isotopic analysis of lipids from pottery, here we investigate the foods prepared by the earliest farming communities of the European Atlantic seaboard. Surprisingly, we find an absence of aquatic foods, including in ceramics from coastal sites, except in the Western Baltic where this tradition continued from indigenous ceramic using hunter-gatherer-fishers. The frequency of dairy products in pottery increased as farming was progressively introduced along a northerly latitudinal gradient. This finding implies that early farming communities needed time to adapt their economic practices before expanding into more northerly areas. Latitudinal differences in the scale of dairy production might also have influenced the evolution of adult lactase persistence across Europe.
Keywords: Carbon Isotopes; zeměpis; Humans; keramika; Dairying; Geography; chov zvířat; archeologie; mléčné výrobky; Agriculture; lipidy; lidé; zvířata; Europe; dějiny starověku; mlékárenství; plynová chromatografie s hmotnostně spektrometrickou detekcí; zemědělství; Ceramics; Archaeology; History, Ancient; Dairy Products; Lipids; Animal Husbandry; izotopy uhlíku; Animals; Gas Chromatography-Mass Spectrometry; Evropa